SULFUR BASED HAZARDOUS WASTE SOLIDIFICATION - Mohamed A.-M.O.; El Gamal M. (My University, 2007)
Existing uses for sulfur are relatively advanced and offer limited opportunities to consume significant new supplies. Currently, sulfur is in net surplus on a global basis, and with environmental regulations, greater sulfur recovery from petroleum and gas processing is mandated. The outlook is clear: there will be substantial and growing surpluses in global sulfur supply in the foreseeable future. Sulfur prices are likely to be under pressure, and producers could face substantial and growing disposal fees. Therefore, new markets must be found for sulfur to avoid disposal crises. One potential new market is the production of sulfur-solidified concrete. This is a thermoplastic composite of mineral aggregates bound together with chemically modified sulfur. The product is more durable than Portland cement. There may be monetizeable benefits in reducing greenhouse gas emissions that would enhance the attraction of sulfur solidified cement applications. The main objective of this study is to evaluate experimentally the potential use of sulfur as a solidifying agent for hazardous waste. To achieve this objective, the study reviewed the sulfur concrete literature, analyzed locally produced sulfur, evaluated a number of sulfur polymer modifiers and physical stabilizing agents, designed a set of experiments and evaluated the produced product for its hydro-mechanical-chemical properties. The results indicated that the manufactured sulfur polymer cement is an excellent candidate for: waste management practices such as solidification/stabilization of hazardous waste; barrier systems for landfilling of hazardous waste; and waste water treatment plants.
Keywords: COMPRESSIVE STRENGTH; DENSITY; FLY ASH; MINERAL FORMATION; MODIFIED SULFUR; MOLTEN SULFUR; MONOCLINIC; ORTHORHOMBIC; SAND; STRUCTURE; TEMPERATURE; VOIDS